Recording of Cash Expenditures and Receipts in School Operational Assistance Funds (BOS) based on Accounting Information Systems at MA Plus Al-Ittihad - Baiq Dewi Lita Andiana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to understand the accounting information system in cash receipts and cash disbursements in school operational assistance funds (BOS). The variables used in this study are Accounting Information Systems, Cash Receipts and Cash Expenditures. The method used in this study is a qualitative method by utilizing data collection techniques and then conducting observations, interviews, documentation, triangulation and literature study. The data used in this study is primary data using observations and interviews with MA Plus Al-Ittihad Bima City. Where the resource persons in this study were the principal, school committee and BOS treasurer at MA Plus Al-Ittihad Bima City. The data analysis technique used is the analysis before in the field, analysis during and after in the field, reducing data, displaying data and drawing conclusions. Based on the results of this study, it shows that the Accounting Information System on the School Operational Assistance (BOS) fund in schools is in accordance with the assistance of an internal control system to be able to produce credible and reliable information and can record errors that have occurred so that they can be corrected in them. There are external controls, administrative controls, operational controls, document controls and security controls. For Cash Receipts, the BOS funds used were based on the technical manual for School Operational Assistance (BOS) funds. In Cash Expenditures on BOS funds, schools have used Regular BOS funds to finance the operational implementation of education in their schools.